Effect of Foreign & Domestic Investment on Manufacturing Industry Performance and Economic Growth (GDP) - Purno, Marhaendro; Purwaningrum, Dwi; Olin, Maria Novita; Yustika, Rida (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines the impact of foreign investment (FDI) and domestic investment (DI) on the performance of the manufacturing sector in Tangerang City and its implications for economic growth, particularly job creation and contribution to GDP. Using a qualitative approach, data were collected from government reports, academic literature, and stakeholder interviews for the period from 2010 to 2023. The results show a significant correlation between increased investment and reduced unemployment. FDI and DI successfully created more than 110,000 jobs, reducing the unemployment rate from 10.5% to 7%. The manufacturing sector's GDP contribution increased from IDR 30 trillion to IDR 52.5 trillion, underscoring the critical role of investment in driving economic growth. Despite facing challenges of low productivity and regulatory barriers, government policies to attract investment and support micro-enterprises have been quite effective in creating a conducive business climate. This study emphasizes the importance of strategic investment and ongoing collaboration for sustainable regional economic growth.